2007
DOI: 10.1016/j.gca.2007.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfer at the mineral/water interface: Selenium reduction by ferrous iron sorbed on clay

Abstract: Electron transfer at the mineral/water interface: Selenium reduction by ferrous iron sorbed on clay. Geochimica et Cosmochimica Acta, Elsevier, 2007, 71 (23) , selenite was sorbed as outer-sphere sorption complex, covering only part of the positive edge sites, as verified by a structure-based MUSIC model and Se K-edge XAS (X-ray absorption spectroscopy). When selenite was added to montmorillonite previously equilibrated with Fe 2+ solution however, slow reduction of Se and formation of a solid phase was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
130
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(138 citation statements)
references
References 84 publications
7
130
1
Order By: Relevance
“…Previous research indicated that aqueous Fe(II) sorbed on solid in heterogeneous solution could quickly reduce Se(IV) to Se(0). 14,40 We propose that the first electron transfer for pyrite-Se(IV) reaction is from Fe 2þ that is adsorbed on pyrite surface to HSeO 3 -, which produces a Fe 3þ . Subsequently, the Fe 3þ receives an electron, at a cathodic site, from Fe 2þ in the mineral surface.…”
Section: Articlementioning
confidence: 99%
“…Previous research indicated that aqueous Fe(II) sorbed on solid in heterogeneous solution could quickly reduce Se(IV) to Se(0). 14,40 We propose that the first electron transfer for pyrite-Se(IV) reaction is from Fe 2þ that is adsorbed on pyrite surface to HSeO 3 -, which produces a Fe 3þ . Subsequently, the Fe 3þ receives an electron, at a cathodic site, from Fe 2þ in the mineral surface.…”
Section: Articlementioning
confidence: 99%
“…Many researchers have reported that Fe(II) is an important factor for inorganic and organic pollutant removal in a ZVI system (Charlet et al 2007;Huang and Zhang 2006). Most of the pollutants can be reduced through redox reactions involving Fe(II) on the Fe(0) surface.…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxides such as magnetite [6], hematite [7][8] and goethite [9] are known to be capable of binding selenite with high distribution coefficients in groundwater without significantly influencing the ionic strength [9]. Moreover, the presence of Fe(II) in magnetite has shown to help the reduction of selenium oxides to a lower oxidation state [5,10] in a pH range of 3~8. However, X-ray absorption spectroscopy (XAS) indicated that the oxidation state of selenium did not change when selenite adsorbed onto magnetite at pH=4.45~7.46 [11].…”
Section: Introductionmentioning
confidence: 99%